2020
DOI: 10.3389/fphy.2020.592875
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Cross-Luminescence in BaF2 for Ultrafast Timing Applications Using Deep-Ultraviolet Sensitive HPK Silicon Photomultipliers

Abstract: Time resolution of scintillation-based detectors is becoming continuously more important, both for medical applications, especially in positron emission tomography (PET), and in high energy physics. This article is an initial study on exploiting the fast cross-luminescence emission in the inorganic BaF 2 scintillator with deep ultraviolet-sensitive silicon photomultipliers (SiPMs) from Hamamatsu for precise timing in PET and HEP. Using small BaF 2 pixels optimized for timing read out by these photodetectors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…In Pots et al (2020) several TCSPC measurements under x-ray excitation of BaF 2 samples from Proteus and Epic Crystal have been performed, placing different filters between the BaF 2 crystal and the single-photon detector, a Becker & Hickl hybrid-PMT. It was found that by placing a high-pass filter of 400 nm (cutting all wavelengths larger than 400 nm) no scintillation emission was recorded.…”
Section: Suppressing the Slow Emission In Baf 2 With 511 Kev Gamma Excitationmentioning
confidence: 99%
“…In Pots et al (2020) several TCSPC measurements under x-ray excitation of BaF 2 samples from Proteus and Epic Crystal have been performed, placing different filters between the BaF 2 crystal and the single-photon detector, a Becker & Hickl hybrid-PMT. It was found that by placing a high-pass filter of 400 nm (cutting all wavelengths larger than 400 nm) no scintillation emission was recorded.…”
Section: Suppressing the Slow Emission In Baf 2 With 511 Kev Gamma Excitationmentioning
confidence: 99%
“…The different experiments performed using the 7 Li enriched crystal and the Asahi optical filter allowed precisely characterizing the material scintillation process. The wavelength-resolved RL results obtained with different photon energies allowed verifying that there is no LET-dependence of the CLYC emission in the range 0.5-5 keV/μm, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were performed with a 1-inch right cylinder CLYC scintillator enriched in 7 Li to > 99%, purchased from Radiation Monitoring Devices [18]. The crystal is hygroscopic and therefore encapsulated in an aluminum housing provided with a single quartz window.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations